THE INTERFACE BETWEEN WTO LAW AND INTERNATIONAL INVESTMENT AGREEMENTS: HISTORICAL DEVELOPMENTS, LEGAL OVERLAPS, AND FUTURE PROSPECTS - Kosimova Gulnoza Odilovna (Innovate Conferences, 2025)
This article explores the evolving relationship between World Trade Organization (WTO) law and International Investment Agreements (IIAs), particularly Bilateral Investment Treaties (BITs). While both regimes were established with different objectives—trade liberalization and investment protection respectively—their legal provisions increasingly intersect in areas such as national treatment, most-favored-nation treatment, and performance requirements. The paper analyzes the historical trajectory of investment regulation in multilateral trade negotiations, particularly within the OECD and WTO, and critically assesses past efforts to create a unified multilateral investment framework. It also considers the implications of this fragmented legal landscape for future harmonization and proposes potential paths forward for integrating investment disciplines within the multilateral trading system.
Keywords: WTO Law, International Investment Agreements, Bilateral Investment Treaties, Multilateral Agreement on Investment, Investment Regulation, Trade and Investment, TRIMs, GATS, Investment Liberalization, Dispute Settlement.